Peran Mahkamah Pidana Internasional Dalam Penanganan Kasus Kejahatan Perang Penghancuran Warisan Budaya di Timbuktu (Studi Kasus Mahkamah Pidana Internasional Nomor ICC-01/12-01/15 Ahmad Al Faqi Al Mahdi) - Ferdiansyah, Diva Salsabila; Prasetyo, Handoyo (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Cultural heritage is closely tied to history and often becomes a victim in armed conflicts, caused by differing national perspectives on economy, politics, and culture. International criminal law, particularly International Humanitarian Law (IHL), protects individuals and civilian objects during conflicts. This research employs a normative-juridical method, involving the analysis of primary and secondary legal materials, using legislative and case approaches, with data collected through library research. The case of Ahmad Al Faqi Al Mahdi, who oversaw the destruction of ten historic sites in Timbuktu in 2012, was prosecuted by the International Criminal Court (ICC) under Article 8(2)(e)(iv) of the Rome Statute. The ICC demonstrated its role in enforcing international criminal law and protecting cultural heritage through new policies and related jurisprudence on war crimes, thereby strengthening the protection of the world's cultural heritage.